**SOLUTION**

Old Ratio (A, B and C) = 4 : 3 : 2

New Ratio (B and C) = 2 : 1**Gaining Ratio = New Ratio − Old Ratio**B’s gain = 2/3-3/9 = 6-3/9 = 3/9

C’s gain = 1/3-2/9 = 3-2/9 = 1/9

**∴Gaining Ratio = 3: 1**

Skip to content
# Blog

## A, B and C were partners sharing profits in the ratio of 4 : 3 : 2. A retires, assuming B and C will share profits in the ratio of 2 : 1. Determine the gaining ratio.

###
Share this content

**SOLUTION**

Old Ratio (A, B and C) = 4 : 3 : 2

New Ratio (B and C) = 2 : 1**Gaining Ratio = New Ratio − Old Ratio**B’s gain = 2/3-3/9 = 6-3/9 = 3/9

C’s gain = 1/3-2/9 = 3-2/9 = 1/9